Optimizing Link Efficiency: Compression Mechanism Analysis in Wide Area Networks An Enterprise Network Case Study - Msiska, Abel; Lubobya, Charles Smart (Faculty of Engineering, Universitas Brawijaya, 2023)
The study aims to analyze the effectiveness of compression mechanisms in optimising link efficiency in Wide Area Networks (WANs). Using an enterprise network as a case study, the researcher employed OPNET Modeler 14.5 for simulation. Three scenarios were simulated, with two using predefined compression mechanisms. Results suggest that a point-to-point network with a compressed layer 2 payload but uncompressed header, achieves higher throughput than one with header compression, or no compression applied. Additionally, layer 2 payload compression reduces both delay and packet loss. The researchers propose a novel Msiska-Lubobya Improved Payload (MLIP) Compression technique to optimize link efficiency for WAN.